Emerging capital markets and transition in contemporary China - Morita, Ken 1947 (World Scientific Publishing Co. Pte. Ltd., 2017)
"This book provides the analysis on capital markets in China, focusing attention upon (1) the bubble phenomena (whether or not a Chinese bubble really exists and might burst), (2) foreign direct investment and (3) integration, through all of which we could recognize the current situation and the future prospects of Chinese marketization. As regards to the bubble phenomena, particularly 'early warning indicator' of the bubble, this book attempts to utilize the Grubbs-Smirnov Test to discover the 'abnormal value' in several asset markets."--Provide by publisher.